2002
DOI: 10.1161/hs0302.104545
|View full text |Cite
|
Sign up to set email alerts
|

Abciximab Bolus Injection Does Not Reduce Cerebral Ischemic Complications of Elective Carotid Artery Stenting

Abstract: Background and Purpose-Abciximab has been shown to significantly reduce thromboembolic complications of coronary artery stenting. A prospective, randomized study was performed to test whether abciximab has comparable beneficial effects in carotid artery stenting. Methods-Seventy-four consecutive patients undergoing elective stenting of the carotid artery were included in the study.Standard antithrombotic medication consisted of aspirin, clopidogrel, and heparin. In addition, half of the patients received an ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 22 publications
(9 reference statements)
0
12
0
3
Order By: Relevance
“…Two abciximab-treated patients developed fatal intracerebral hemorrhage. Hofmann et al 11 had similar observation in a randomized comparison between abciximab bolus prior to the procedure and standard antithrombotic treatment. The 37 patients who received abciximab experienced 4 TIAs, 1 minor stroke, 1 major stroke, and 1 fatal stroke (overall rate of 19%) compared to 8% (2 TIAs and 1 major stroke) in the 37 patients who received standard treatment.…”
mentioning
confidence: 72%
“…Two abciximab-treated patients developed fatal intracerebral hemorrhage. Hofmann et al 11 had similar observation in a randomized comparison between abciximab bolus prior to the procedure and standard antithrombotic treatment. The 37 patients who received abciximab experienced 4 TIAs, 1 minor stroke, 1 major stroke, and 1 fatal stroke (overall rate of 19%) compared to 8% (2 TIAs and 1 major stroke) in the 37 patients who received standard treatment.…”
mentioning
confidence: 72%
“…However, this was not confirmed in a randomized, controlled trial. 25 The incidence of TIA or strokes was not significantly different with the use of abciximab in addition to standard antithrombotic therapy. Another study in fact found a higher incidence of intracerebral hemorrhages in patients who had recent cerebral ischemic events.…”
Section: Measures To Reduce Complications With Stentingmentioning
confidence: 90%
“…18 The routine use in carotid artery stent placement was discontinued after a randomized trial, and 2 single-center comparisons with historical controls did not demonstrate any reduction in periprocedural ischemic events. [19][20][21] The relatively high rate of fatal intracerebral hemorrhages (ICHs) observed in studies also reduced the enthusiasm for using these agents. 22 Some local institutional review boards may require that planned use of these agents involve informing patients or relatives regarding such complications.…”
Section: Platelet Glycoprotein Iib/iiia Inhibitorsmentioning
confidence: 99%